Co-determination and industrial democracy. Tribute to Walther Müller-Jentsch - Köhler, Holm-Detlev (Cuadernos de Relaciones Laborales, 2026)
A reflection on the work and life of the recently deceased great German sociologist Walther Müller-Jentsch serves to revisit the main debates about industrial relations from World War II to the present and clarify the nature of this subdiscipline as a dynamic set of institutions and social relations. Industrial relations are not a system or a structure, much less a set of rational decisions, but rather a complex of interests and actors in constant conflict and evolution. Basic concepts developed by Müller-Jentsch, such as conflict partnership (Konfliktpartnerschaft), co-determination, industrial citizenship, and economic democracy, reflect this dynamic and conflictual nature in the debates of sociology of work. Analyzing labor relations thus implies analyzing society in its development and its structuring conflicts.